Dinuclear NHC gold(I) allenyl and propargyl complexes: an experimental and theoretical study - Zargaran, Poorya; Mulks, Florian; Gall, Samuel; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organometallics, 2019)
The synthesis and isolation of the dinuclear NHC gold(I) allene-1,3-diyl complex Ph(IPrAu)C═C═CH(AuIPr) and the dinuclear NHC gold(I) propyne-1,3-diyl complex Ph(IPrAu)CH–C≡C–Au(IPr) are presented. The monoprotodeauration reactions of these dinuclear complexes selectively led to the mononuclear organogold complexes Ph(IPrAu)C═C═CH2 and PhCH2–C≡C–Au(IPr), respectively. The experimental structures and the obtained analytical data of the synthesized complexes as well as the results of a computational DFT study of their thermodynamic stability are compared systematically.
Gesehen am 13.05.2019